Integrated Analysis Highlights the Immunosuppressive Role of TREM2+ Macrophages in Hepatocellular Carcinoma - Zhou, Lisha; Wang, Meiling; Guo, Hanrui; Hou, Jun; Zhang, Yingna; Li, Man; Wu, Xiangwei; Chen, Xueling; Wang, Lianghai (Frontiers in Immunology, 2022)
Recently, attention has been focused on the central role of TREM2 in diverse pathologies. However, the role of TREM2 signaling in the tumor microenvironment of hepatocellular carcinoma (HCC) remains poorly understood. Herein, we systematically investigated the single-cell transcriptomes of human HCC tissues and found that TREM2 was predominantly expressed by a macrophage subpopulation enriched in tumor tissues that resemble lipid-associated macrophages (LAMs). The accumulation of TREM2+ LAM-like cells in HCC was confirmed in two additional cohorts using scRNA-seq analysis and immunohistochemistry. High expression of TREM2 correlated with high infiltrating macrophage abundance and poor prognosis. Based on systematic interrogations of transcriptional profiles and cellular interactions, TREM2+ LAM-like cells were identified to mainly originate from S100A8+ monocytes and represented an immunosuppressive state. TREM2+ LAM-like cells recruited suppressive Treg cells, facilitating microenvironment remodeling. Furthermore, gene regulatory analysis and in vitro functional assays indicated that activation of LXR signaling could promote the reprogramming of TREM2+ LAM-like cells. Correlation analysis of bulk RNA-sequencing data demonstrated that the enrichment of TREM2+ LAM-like cells was an independent indicator of adverse clinical outcomes in HCC patients. Our comprehensive analyses provide deeper insights into the immunosuppressive role of TREM2+ LAM-like cells in HCC.